Flood resilience in the context of shifting patterns of risk, complexity and governance: An exploratory case study - Johnson Noel; McGuinness Martina (E3S Web of Conferences, 2016)
This paper presents a case study of an industrial locale in the United Kingdom which has come together in an innovative governance structure to respond to the risk of flooding. Public and private sector bodies have joined together to establish a ‘business improvement district’ (BID), the sole purpose of which is to build resilience to future flooding events. More specifically, we examine the effectiveness of this strategy as a mechanism for capacity building within the small and medium sized enterprise sector. This is an important area of study as small and medium sized enterprises (SMEs) are particularly vulnerable to the negative impacts of a flood event, as they possess fewer resources than their larger counterparts leaving them with less capacity and organisational slack to respond to a major disruption. Drawing upon primary and secondary data, we identify both institutional barriers and enablers to the development of novel responses to flooding.